Is virtual clinic follow-up of hip and knee joint replacement acceptable to patients and clinicians? A sequential mixed methods evaluation. Issue 1 (1st March 2019) - Parkes, Rebekah J; Palmer, Joanne; Wingham, Jennifer; Williams, Dan H
Abstract : Objective: To evaluate the acceptability to key stake holders of a newly introduced virtual clinic follow-up pathway for hip and knee joint replacement. Design: A service evaluation comprising a questionnaire sent electronically to 115 patients and interviews with 10 individuals. Setting: A newly introduced virtual clinic follow-up pathway for hip and knee replacement patients in a district general hospital. Participants: The electronic questionnaire was distributed to all patients treated under the virtual clinic service over a 5-month period (n=115). Purposive sampling from volunteers among respondents, leading to semi-structured interviews with eight patients. Two orthopaedic consultants were also interviewed. Intervention: Consultant review of web-based patient reported outcome measures and digital radiographs, with feedback to patients via letter, replacing face-to-face outpatient appointments for the follow-up of hip and knee joint replacement. Results: The response rate to the questionnaire was 40%. 44% indicated they would prefer a virtual appointment over a face-to-face consultation in future. The most common word in the free text comments was 'good' (n=107). Seven main themes were identified from the patient interviews: patient understanding and expectations, patient confidence, patient voice, managing deterioration of condition, patient benefit, patient satisfaction using technology and navigating the website. Two main themes were identified from the staff interviews: the adapting patient pathway and project management. Combined analysis elucidated that patients who were doing well liked the 'click and go' approach but those with problems were concerned about how to report these and were therefore less satisfied. Conclusion: The virtual clinic process appears to be well accepted by both patients and clinicians. However, appropriate patient selection and clear pathways of communication to address patient concerns are pivotal to success.